Research on music teaching in Early Childhood education: what the academic productio says (Research, Society and Development, 2022)
The article aims to understand which are the burning themes related to music teaching in Early Childhood Education. Based on principles related to the teaching of music in Early Childhood Education, we carried out a qualitative analysis of a set of 13 articles available in the repositories of Scielo, Capes, Revista da Abem and Revista Música Hodie. The empirical material of the study was analyzed based on content analysis, from which we identified/understood the main themes related to music teaching in Early Childhood Education, that is: the teachers' musical practices and interactions/relationships; musicalization in Early Childhood Education; the educational social environment; the cartographic experience; the biographical narrative; the teaching of music in Early Childhood Education; the processes of appropriation of music by children; and the musical repertoire for children.